Pengaruh Konten TikTok terhadap Revisit Intention Wisatawan Generasi Z di Kawasan Blok M Jakarta - Rifa Muhamad Rizki; Sheidy Yudhiasta (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of TikTok content on the Revisit Intention of Generation Z tourists in the Blok M area, Jakarta. The rapid growth of social media, particularly TikTok through its For You Page (FYP) feature, has transformed the way young tourists obtain information and make travel decisions. Blok M has recently experienced urban regeneration and emerged as a creative and culinary destination frequently promoted through TikTok content. This research employed a quantitative associative approach using purposive sampling techniques. Data were collected from 30 Generation Z respondents who had been exposed to TikTok content about Blok M and had visited the destination at least once. The data were analyzed using simple linear regression. The findings indicate that the research instrument is valid and reliable and meets the normality assumption. The regression results reveal that TikTok content has a positive and significant effect on Revisit Intention (t = 15.013; p < 0.001). Furthermore, the coefficient of determination shows that TikTok content explains 88.9% of the variance in revisit intention. These findings suggest that visual attractiveness, information quality, and content authenticity on TikTok play an important role in encouraging repeat visits among Generation Z tourists. The study contributes to the growing literature on digital tourism marketing and urban destination management.